2013
DOI: 10.1148/radiol.13121451
|View full text |Cite
|
Sign up to set email alerts
|

3.0-T MR Imaging of Intracoronary Local Delivery of Motexafin Gadolinium into Coronary Artery Walls

Abstract: Purpose:To develop a technique with clinical 3.0-T magnetic resonance (MR) imaging to delineate local contrast agent distribution in coronary artery walls for potential molecular MR imaging-guided local gene or drug therapy of atherosclerotic coronary artery disease. Materials and methods:This animal protocol was approved by the institutional animal care and use committee and was in compliance with the Guide for the Care and Use of Laboratory Animals. For in vitro confirmation, human arterial smooth muscle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Results of previous studies (19)(20)(21)(22) have confirmed that MGd can be internalized exclusively in metabolically active tissues, such as atherosclerotic plaques and different tumors. It also can cross the disrupted blood-brain barrier associated with brain tumors, but it is not detectable in normal brains (18,23,24).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Results of previous studies (19)(20)(21)(22) have confirmed that MGd can be internalized exclusively in metabolically active tissues, such as atherosclerotic plaques and different tumors. It also can cross the disrupted blood-brain barrier associated with brain tumors, but it is not detectable in normal brains (18,23,24).…”
Section: Discussionmentioning
confidence: 61%
“…Qiu et al T1-weighted MR imaging contrast agent, and a red fluorescence emitter (19)(20)(21). In the current study, we attempted to investigate the application of MGd for intraoperative imagingguided complete glioma resection.…”
Section: Experimental Studies: Motexafin Gadolinium-enhanced Moleculamentioning
confidence: 99%
“…Finally, three groups utilized the signal-to-noise ratio (SNR) to analyze the region of interest [10,13,16]. e SNR was calculated by dividing the signal intensity of the samples by the standard deviation of the background noise [17]. Finally, one group utilized the percentage normalized enhancement (%NENH) between the intestine and liver for quantitative evaluation [16].…”
Section: Molecular Imaging and Improved Diagnosticsmentioning
confidence: 99%
“…Recent rapid advances in cancer therapy include image-guided, minimally invasive interventional oncology techniques [ 19 , 20 ]. Previous studies from our group indicated that a combination treatment with local heat-controlled chemotherapy and interventional radiofrequency hyperthermia (RFH) enhances the therapy of various types of malignancies [ 21 23 ]. These results encouraged us to develop a new oncologic therapy technique, employing interventional mild RFH for enhanced heat-controlled suicide gene therapy, to solve the problem of multidrug resistance in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%